Political disputes and consequences on tourism - Liasidou, Sotiroula (My University, 2018)
The aim of the paper is to identify the stance of tourism industry practitioners in the Republic of Cyprus in the case of reunification. Since 1974 and the Turkish invasion, one third of the island's territory has remained under an illegal occupation. Discussing Cyprus' political problem and the potential of reunification in relation to the tourism industry is a new concept in nature. The tourism industry will be the vehicle for further economic development. So, it is imperative to understand the opinions of tourism stakeholders and decision makers who will potentially be involved in the development of tourism in the reunited island. In order to identify the consequences of the status quo on the Republic, the views of 26 powerful elite people, both in the public and private sectors of the country, were collected through a qualitative data inquiry using semi-structured interviews. The results of the study suggest that the inability to come up with a viable solution has many negative consequences on the tourism industry of the island. The results of the study suggest that a possible reunification will render Cyprus as an innovative tourism destination.
Keywords: Tourism industry; Cyprus; Political disputes; Interviews